2020
DOI: 10.1109/access.2020.2973679
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Highly Nonlinear and Dynamic AES Substitution-Boxes (S-Boxes) Using Chaos-Based Rotational Matrices

Abstract: This work reports a novel chaos-based affine transformation generation method, which is based on rotational matrices to design strong key-based S-boxes. Chaotic logistic map's nonlinear trajectories are used to generate rotational matrices under given design conditions. Thus, the inherent logic is to generate key-based S-boxes, as strong as AES S-box, in terms of cryptographic properties using chaos in affine transformation. The randomness of chaotic sequences is tested using the National Institute of Standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…This is because an S-box is a consistent element that is nearly always at the core of image encryption algorithms and is tasked with applying Shannon's property of confusion. In order to evaluate the ability of an S-box to cause confusion, 5 metrics are commonly computed [46]. These are the non-linearity (NL), linear approximation probability (LAP), differential approximation probability (DAP), bit independence criterion (BIC) and strict avalanche criterion (SAC).…”
Section: S-box Performance Analysismentioning
confidence: 99%
“…This is because an S-box is a consistent element that is nearly always at the core of image encryption algorithms and is tasked with applying Shannon's property of confusion. In order to evaluate the ability of an S-box to cause confusion, 5 metrics are commonly computed [46]. These are the non-linearity (NL), linear approximation probability (LAP), differential approximation probability (DAP), bit independence criterion (BIC) and strict avalanche criterion (SAC).…”
Section: S-box Performance Analysismentioning
confidence: 99%
“…Because Ref. [40][41][42][43][44][45] is based on mathematical transformations. It can be observed that these designs are closed to ideal values for both the nonlinearity criterion and the XOR value.…”
Section: A Practical Application Of Generated Random Bit Sequencesmentioning
confidence: 99%
“…In the approaches suggested in Ref. [43][44][45], the design criteria have been reached. It has also been shown in different studies that a similar approach can be achieved by optimizing the results [46,47].…”
Section: A Practical Application Of Generated Random Bit Sequencesmentioning
confidence: 99%
“…Recently, chaos theory has been a major focus and gained the attention of many S-Box designers to create this nonlinear component of modern block ciphers [21,22]. In order to build robust S-Boxes, authors in [23] developed a novel technique based on Logistic chaotic map that employed the idea of matrix rotation and affine transformation to generate key-dependent S-Boxes. Four steps that make up the suggested process for S-Box construction include the calculation of the Galois Field inverse, creating keys using Logistic map, computing the rotational matrix, and ultimately creating a new S-Box.…”
Section: Introductionmentioning
confidence: 99%